HUBUNGAN KUALITAS PELAYANAN, KEPUASAN DAN LOYALITAS PENGGUNA OJEK SEPEDAMOTOR - Bahar, Taslim; Tamin, Ofyar Z. (MEKTEK, 2010)
Perceived service quality and satisfaction by users is important aspects on service decision making of travel mode choice. Ojek motorcycle (MC) is an informal public transport recently tends to increase used for short distance in Indonesia cities. This study aim to investigate effect and the relationships of service quality, satisfaction and loyalty of usage of ojek’s MC. the study employs a questionnaire survey and home interviews for ojek’s MC users in Bandung City. The analysis is conducted by using structural equation modeling (SEM). The study’s results are as follows: from second order confirmatory factor analysis, it’s found that time reliability and accessibility factors are significant reflection of service quality, but environment factor is not significant. From analysis the structural relationships between latent variables, it is found that service quality influence directly and significantly to satisfaction and then affect loyalty. Finally, it concludes that the ojek’s MC is still popularity used for urban passenger’s public transport, especially for short distance in Indonesia cities